Morphological diversity and genetic structure of cultivated Bougainvillea germplasm collected from Vietnam, Laos, and Thailand - HAI THI HONG TRUONG; NHAN VAN NGUYEN; NHI THI HOANG HO; HIEU HOANG TRUNG NGUYEN; HAN NGOC HO; CHUONG VAN HUYNH (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Truong HTH, Nguyen NV, Ho NTH, Nguyen HHT, Ho HN, Huynh CV. 2026. Morphological diversity and genetic structure of cultivated Bougainvillea germplasm collected from Vietnam, Laos, and Thailand. Biodiversitas 27 (1): d270141. https://doi.org/10.13057/biodiv/d270141. Bougainvillea is a major ornamental genus widely cultivated across tropical regions, yet germplasm from Southeast Asia remains poorly characterized. This study aimed to assess the genetic diversity and population structure of 33 Bougainvillea accessions from Vietnam, Laos, and Thailand using an integrated analysis of nuclear ribosomal ITS sequences, RAPD markers, and DUS-based morphological traits. ITS phylogeny clearly delimited two species, B. glabra and B. spectabilis, and revealed moderate sequence variation (π = 0.03299; Hd = 0.68; six haplotypes). RAPD profiling showed a high proportion of polymorphic bands (91.54%) and moderate genetic diversity, resolving the accessions into six genetic clusters, including a distinct singleton accession (T7). Morphological characterization based on 21 qualitative traits revealed substantial phenotypic variation, particularly in bract-related traits, and separated accessions into two major morphological groups, with consistent outliers (V1, V18, and V24). Overall, the combined morphological and molecular evidence demonstrated concordant patterns of species delimitation and cultivar-level differentiation, indicating that ITS is effective for resolving species boundaries. In contrast, RAPD provides higher resolution among cultivated materials. These results provide a practical basis for germplasm authentication, redundancy management, and the identification of genetically unique accessions, such as T7, V1, V18, and V24. This process will assist in conservation efforts and parent selection, ultimately supporting the breeding and sustainable use of Bougainvillea in Southeast Asia.